(3GdCQb YOh GdUMI hGdfLGMs 40 (3fUjMI deSGYOJc Ydj Gdfhe GdgGOF hQGMI GdHGds - (3GdMSjfj (B, (3Cjefs (3eDdas; (3EHQGgje (B, (3EHQGgje eMeOs (3JUeje GdZdGas ((3GdbGgQIs (3OGQ GdWdGFY ddfTQ hGdJhRjYs, 2001)
(3YfOeG jNdO cd efG Edi aQGTg aEfg jefi faSg HSGYGJ ef fhe gGOF Yejb jQjMg ef YfGA jhe Yed TGb , hjYjO Edi LSeg MjhjJg hjLOO Hg fTGWg hbhJg aGdfhe ddEfSGf gh HeKGHI hbaI eDbJI dJbdjd GdeLghO GdPj JHPdg CLgRI GdLSe GdeJYOOI aJCNP bSWG ef GdQGMI JSJWjY HYOg Cf JYhO Edi SGHb YgOgG Ohf CjI JCKjQGJ VGQI CeG EPG de Jcf gfGc gPg GdhbaI aEf ELgGOG eDKQG Sha jUjH GdCLgRI jJHYg VZhW YUHjI PGJ eVGYaGJ NWjQI bO JhOi HMjGI GdEfSGf aj HYV GdCMjGf (B! (3hef Ke cGf dGHO ef JhajQ efGN efGSH daJQI Gdfhe GdJj jbJWYgG GdEfSGf ef hbJg hdeG cGf GdHYV jUGH HMGdI ef GdCQb YfOeG jChi Edi GdaQGT aEfg ef GdhGLH Ydjg CdG jSJSde dPdc , hCdG jdLC ddCbQGU GdefheI aj LejY GdCMhGd , dCf GdGYJjGO Ydi gPg GdcjeGhjGJ dg BKGQ LGfHjI JVQ HCLgRI NQi ef CLgRI GdLSe hef GdVQhQj Cf jaJT GdTNU aj LejY GdCSHGH GdJj JMhd Ohf JeJGYg HGdfhe GdeWdb(B. (3hbO MGhd eDda gPG GdcJGH Cf jJNdd LejY aP GdCQb HGMKG Yf WQb YdGLgG hGdJNdU efgG ShGA cGf Pdc HJfGhd SGH eYjfI , Ch HGdHYO Yf GdYGOGJ GdJj JDOi ai GdfgGjI Edi GdCQb hYOO jGM aj Gdfhe (B. (3Ef gPG GdcJGH dG jUfY GdeSJMjd hdcfg jCNP Hj` MU djVYgG Ydi ehWf GdYdI , hjJHbi Ydi GdTNU Cf jLJgO a` GdfUGFM GdeSOGI Edjg MJi jJNdU JeGeG ef eTcdI YOe GdGSJZQ he , hCf jYjO Edi faSg QGMJgG GdeSdhHI , hCf jbHd Ydi ZOg (B- (3eTQb dG jThHg GdJhJQ hGdGfaYGd GdfGLejf Yf MGdGJ Ji cGfJ JYJQjg ef bHds
Keywords: (3GdGQbs -- (3GdWH GdfaSjs